Pengaruh Harga, Promosi, Lokasi dan Kualitas Pelayanan terhadap Keputusan Rahin Memilih Gadai Emas di PT Bank BJB Syariah KCP Arcamanik Bandung - Rahayu, Wina; Rapida, Ida Rapida (Masoem University, 2024)
Based on the results of initial research, that the background of this study is the fluctuation in the number of rahin. This is thought to have something to do with price, promotion, location and quality of service to rahin's decision. This study aims to determine how the influence of price, promotion, location and service quality on rahin's decision to choose a gold pawn at PT Bank BJB Syariah KCP Arcamanik Bandung, both partially and simultaneously. The object of research is rahin at PT Bank BJB Syariah KCP Arcamanik Bandung. Research is quantitative associative. Population rahin 125 people, determination of samples with the Slovin formula amounted to 56 people. Data collection techniques include observation, interviews, literature studies and questionnaires. The questionnaire was distributed through google form, then data analysis using the help of SPSS. The results showed that each variable either partially or simultaneously had an influence on the decision of rahin to have a gold pawn at PT Bank BJB Syariah KCP Arcamanik Bandung. Partially the price variable has an effect 20,3%, promotion has an effect 10,8. %, location has an influence 54,4 %, service quality matters 83,5% against the decision of the trahin. While simultaneously the independent variables affect 32,8% on the variability of rahin decision.